Evaluating the effectiveness of Integrated STEM-lab activities in improving secondary school students' understanding of electrolysis. Issue 3 (16th May 2019) - Daman Huri, Noor Haslina; Karpudewan, Mageswary
Abstract : STEM education is gaining increasing attention globally to fulfill the acute shortage of STEM workforce. Executing STEM education is frequently viewed as a complex and challenging agenda. The current study proposes Integrated STEM-lab activities in the teaching and learning of electrolysis. The activities use real-world contexts as a platform to exhibit the transdisciplinary nature of integration of the four STEM disciplines. Embedded mixed methods research used quantitative one group pre-test–post-test design, and qualitative interviews were employed to measure the effectiveness of the Integrated STEM-lab activities in improving 50 secondary school students' (Form Four equivalent to Grade 9) understanding of electrolysis. The Electrolysis Diagnostics Instrument was administered for pre- and post-tests. One-way Multivariate Analysis of Variance (MANOVA) revealed that the Integrated STEM-lab activities effectively improved the students' understanding of electrolysis measured in three subscales (Wilks' lambda = 0.664; F (3, 96) = 16.164; p < 0.05; η = 0.336) with 33.6% of the variances in the pre- and post-tests explained by the treatment. The qualitative interview data supported and provided insight into understanding the quantitative findings. In the interviews, the students elaborated their understanding of electrolysis with details, and consistently the activities were referred to in their responses. The findings of this study suggest that Integrated-STEM lab activities are suitable to address the limitation of the existing laboratory activities for knowledge construction. The activities are exemplary for integrating the four STEM disciplines into the standard science curriculum.